CUSTOMARY CONFLICT AND BANISHMENT ‘KASEPEKANG’ AT BUNGAYA TRADITIONAL VILLAGE, KARANGASEM REGENCY, BALI: IN THE PERPECTIVE OF CULTURAL STUDIES - Windia, I Wayan; Parimartha, I Gde; Putri Astita, Tjok Istri; Drama Putra, Nyoman (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2009)
-